Mass Media’s Racist Reportage about Russian Invasion of Ukraine - Mirza Fathima Jauhar Kamalia; Dheny Djatmiko (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2022)
This study discusses the mass media’s racist report about the Russian invasion of Ukraine. This research is analyzed by using Orientalism. This study uses qualitative methods supported by the data from some mass media like CBS, Al-Jazeera, Hareetz.com, and Channel 4 News, articles, and books that are relevant to this study. The results of this study are These reportages show the depiction of the West as 1) civilized; 2) prosperous, middle class, and well-dressed; 3) intelligent and educated; 4) priority. All of the depictions of the West above affect the audiences by internalizing them in their mind, starting to agree with and believe them. It will strengthen the belief of the West as the most superior nation among the other nations and—as the result—their position is the highest among the others. These beliefs will lead to racism and ethnocentrism in the West. Keywords: Mass Media, Racist, Orientalism.